2001
DOI: 10.1097/00000539-200101000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Venous Pressure as a Hemodynamic Variable in Neurosurgical Patients

Abstract: In patients undergoing either elective craniotomy or complex spine surgery, peripheral venous pressure (PVP) trends correlated with central venous pressure (CVP) trends with a mean offset of 3 mm Hg (PVP > CVP). PVP trends provided equivalent physiological information to CVP trends in this subset of patients, especially during periods of hemodynamic instability. In addition, measurements made during a planned circulatory arrest support the hypothesis that PVP approximates mean systemic pressure (systemic arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 20 publications
5
42
0
2
Order By: Relevance
“…Previously, some clinicians have introduced PVP, a simple and less invasive hemodynamic monitoring variable, as an alternative to CVP and found various correlations between them. [16][17][18][19][20][21][22] However, the use of PVP in place of CVP has not been widely advocated in the past because peripheral veins have valves that may interrupt the continuous column of blood and are thinwalled, and may be more easily subjected to compression and occlusion by the surrounding soft tissues. 21 In addition, external compression by the operator or blood pressure cuff and overstretching in the catheterized arm can occlude the peripheral vein and increase PVP, and muscle movement and shivering can be other sources of interference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, some clinicians have introduced PVP, a simple and less invasive hemodynamic monitoring variable, as an alternative to CVP and found various correlations between them. [16][17][18][19][20][21][22] However, the use of PVP in place of CVP has not been widely advocated in the past because peripheral veins have valves that may interrupt the continuous column of blood and are thinwalled, and may be more easily subjected to compression and occlusion by the surrounding soft tissues. 21 In addition, external compression by the operator or blood pressure cuff and overstretching in the catheterized arm can occlude the peripheral vein and increase PVP, and muscle movement and shivering can be other sources of interference.…”
Section: Discussionmentioning
confidence: 99%
“…16 But PVP waveforms appear as a more dampened sinusoidal pattern. 16,17 The inability of PVP waveforms to obtain useful information on cardiac function may not jeopardize the living liver donors because most of them are in healthy condition without cardiovascular diseases. CVP changes with respiratory cycle during mechanical ventilation in relation to the changes in intrathoracic pressures, and CVP is increased by both positive pressure ventilation and positive end-expiratory pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies employing invasive and non invasive techniques showed a good correlation between peripheral venous pressure and CVP under a variety of study conditions in the operating room and the intensive care unit. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Basis for these studies is the fact, that in supine position pressure values within the cephalic, basilic and brachial veins are nearly identical to those of the superior vena cava. 4,5,19 Measurements of the inferior vena cava (IVC) diameter using ultrasound is frequently used to assess volume status of critically ill patients 20,21 , primarily distinguishing hypo-from iso-and hypervolemic conditions.…”
Section: Introductionmentioning
confidence: 99%